Left Dorsolateral Prefrontal Cortex Glx/tCr Predicts Efficacy of High Frequency 4- to 6-Week rTMS Treatment and Is Associated With Symptom Improvement in Adults With Major Depressive Disorder: Findings From a Pilot Study - Bhattacharyya, Pallab; Anand, Amit; Lin, Jian; Altinay, Murat (Frontiers in Psychiatry, 2021)
About 20-40% of estimated 121 million patients with major depressive disorder (MDD) are not adequately responsive to medication treatment. Repetitive transcranial magnetic stimulation (rTMS), a non-invasive, non-convulsive neuromodulation / neurostimulation method, has gained popularity in treatment of MDD. Because of the high cost involved in rTMS therapy, ability to predict the therapy effectiveness is both clinically and cost wise significant. This study seeks an imaging biomarker to predict efficacy of rTMS treatment using a standard high frequency 10-Hz 4- to 6-week protocol in adult population. Given the significance of excitatory and inhibitory neurotransmitters glutamate (Glu) and gamma aminobutyric acid (GABA) in the pathophysiology of MDD, and the involvement of the site of rTMS application, left dorsolateral prefrontal cortex (lDLPFC), in MDD, we explored lDLPFC Glx and GABA levels, measured by single voxel magnetic resonance spectroscopy (MRS) with total creatine (tCr; sum of creatine and phosphocreatine) as reference, as possible biomarkers of rTMS response prediction. MEGA-PRESS MRS data from 7 patients (40-74 y) were used in the study; 6 of these patients were scanned before and after 6 weeks of rTMS therapy. Findings from this study show strong inverse correlation between pretreatment lDLPFC Glx/tCr and (i) posttreatment depression score and (ii) change in depression score, suggesting higher Glx/tCr as a predictor of treatment efficacy. In addition association was observed between changes in depression scores and Glx/tCr ratio. The preliminary findings did not show any such association between GABA/tCr and depression score.